EFEKTIVITAS EDUKASI DAN BIMBINGAN KADER DALAM PENCEGAHAN DAN PENGELOLAAN TUBERKULOSIS - Salma Radiatul Aisi; Lilis Lismayanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Tuberculosis (TB) remains a global and national health problem, with Indonesia ranking second in the world for the highest number of TB cases. Low public awareness, stigma, and non-compliance with treatment are major obstacles to TB control. Community-based strategies, particularly through education and cadre involvement, are considered important for strengthening TB prevention and treatment efforts. However, their effectiveness has not been systematically summarized. This study aims to analyze the effectiveness of community cadre education and guidance in TB prevention and management through a literature review from Google Scholar and the Garuda Portal. Selection was based on year of publication, topic relevance, full-text availability, and focus on community intervention. Of the 2,490 articles identified, 60 articles were screened based on their titles and abstracts, 37 articles were evaluated in full text, and 5 articles met the inclusion criteria for analysis using a thematic approach. The results show that community education increases knowledge about TB symptoms and prevention, while cadre involvement accelerates early detection, improves OAT adherence, and reduces stigma. The role of cadres also contributes to an increase in TB suspect referrals and treatment success, although challenges such as limited training and access to services still exist. Overall, cadre education and guidance have proven effective in strengthening TB prevention and management. Strengthening cadre training, improving continuing education, and providing social support are necessary to support the success of TB elimination programs.